Design, syntheses and evaluations of novel indole derivatives as orally selective estrogen receptor degraders (SERD). Issue 22 (15th November 2020) - Dong, Jiaqiang; Wang, Tie-lin; Lu, Jianyu; Ding, Charles Z.; Hu, Lihong; Hu, Guoping; He, Huijun; Zeng, Xu; Li, Xiaoting; Sun, Deheng; Zhu, Yingjie; Shen, Liang; et al.
Graphical abstract: Abstract: Most estrogen receptor positive (ER +) breast cancers depend on ER signaling pathway to develop. Clinical application of SERD fulvestrant effectively degraded ER, blocked its function and prolonged progression free survival of ER + breast cancer patients. However, current SERD suffers from limited bioavailability, therefore is given as intramuscular (IM) injection. In this paper, we report herein a novel indole series compounds with nanomolar range ER degradation potencies and oral systemic exposures. Selected compounds suppressed tumor growth in vivo in ER + MCF7 breast cancer CDX model via p.o. administration. All those data supported further optimizations of this analog to develop preclinical candidate as oral SERD for ER + breast cancer's treatment.